Mechanism of Electroacupuncture Against Cerebral Ischemia–Reperfusion Injury: Reducing Inflammatory Response and Cell Pyroptosis by Inhibiting NLRP3 and Caspase-1 - Cai, Li; Yao, Zeng-Yu; Yang, Lu; Xu, Xiu-Hong; Luo, Meng; Dong, Miao-Miao; Zhou, Guo-Ping (Frontiers in Molecular Neuroscience, 2022)
Abstract Cell pyroptosis is one of the main forms of neuronal injury after cerebral ischemia-reperfusion. It is accompanied by inflammatory reaction and regulated by caspase gene family. Electroacupuncture can reduce neuronal injury caused by cerebral ischemia-reperfusion, we speculate that electroacupuncture can prevent neuronal pyroptosis after cerebral ischemia-reperfusion by regulating NLRP3/ caspase-1 pathway. The cerebral ischemia-reperfusion injury model of C57 and Cas-1 ko mice was established by longa’s method. Electroacupuncture was conducted at acupoints Chize (LU5), Hegu (LI4), Sanyinjiao (SP6), and Zusanli (ST36) 1.5 hours after cerebral ischemia-reperfusion injury for 20 minutes, and observation was carried out after 24h. Neurological deficit scores evaluated the neurological function, cerebral infarction volume was observed by TTC staining, HE staining, TUNEL and caspase-1 double-labeled fluorescence staining, NLRP3 and caspase-1 double-labeled immunofluorescence staining were used to observe the morphology of neurons in hippocampus, and the protein expression of NLRP3, pro caspase-1, cleaved csapase-1 p20, pro IL-1β, cleaved IL-1β, GSDMD was detected by Western blot assay. Results showed that electroacupuncture could reduce the score of neurological deficit, reduce the volume of cerebral infarction and improve the degree of nerve cell injury, and inhibit NLRP3, pro caspase-1, cleaved csapase-1 p20, pro IL-1β, cleaved IL-1β, GSDMD protein expression. In summary, electroacupuncture plays a neuroprotective role by reduce the pyroptotic neurons which were caspase 1-mediated and inflammatory response after cerebral ischemia-reperfusion.